Pengaruh Liquidity, Leverage Dan Firm Size Terhadap Financial Distress Pada Perusahaan Manufaktur - Teresa Minardi Chai Tony Sudirgo (Jurnal Paradigma Akuntansi, 2021)
This research's purpose is to obtain empirical evidence about the effect of liquidity, leverage, and company size on financial distress. This research was conducted using secondary data. The object of this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2017 - 2019. This research was conducted with a sample size of 20 manufacturing companies and a total of 60 samples of company data for 3 consecutive years. Furthermore, the data collection technique used in this study was purposive sampling that was processed using the EViews version 10.0 program. The results showed that all independent variables in this study had a simultaneous influence on financial distress (F test). The t test results show that liquidity (CR) has a positive and insignificant effect on financial distress, while leverage (DAR) has a significant positive effect on financial distress. For company size (SIZE), this variable has a positive and insignificant effect on financial distress.